2010
DOI: 10.1016/j.tree.2009.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up from gardens: biodiversity conservation in urban environments

Abstract: As urbanisation increases globally and the natural environment becomes increasingly fragmented, the importance of urban green spaces for biodiversity conservation grows. In many countries, private gardens are a major component of urban green space and can provide considerable biodiversity benefits. Gardens and adjacent habitats form interconnected networks and a landscape ecology framework is necessary to understand the relationship between the spatial configuration of garden patches and their constituent biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
853
0
53

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,254 publications
(925 citation statements)
references
References 110 publications
19
853
0
53
Order By: Relevance
“…UA is connected to multiple metabolic pathways in the urban ecosystem including food provisioning (Zezza & Tasciotti, 2010), regulation of local microclimate and hydrology (Oberndorfer et al, 2007), consumption of nutrient rich "waste" water and biosolids/organic matter (Armstrong, 2009;de Zeeuw et al, 2011;Smit & Nasr, 1992), and fixation of atmospheric nitrogen (Herridge et al, 2008) and carbon (Beniston & Lal, 2012). For pollinators and other wildlife, habitat is created in the city (Goddard et al, 2010). It has been suggested that UA can also alleviate poverty (van Veenhuizen & Danso, 2007;Zezza & Tasciotti, 2010), increase resiliency (to market fluctuations and climate change) (de Zeeuw et al, 2011), serve as a repository of agricultural knowledge (Koohafkan & Altieri, 2010) and an incubator of new technologies (Despommier, 2010), provide measurable improvements to human health and wellbeing (Joye, 2007;Ulrich, 2006), and reunite urbanites with natural systems from which they have been separated (McClintock, 2010;Turner, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…UA is connected to multiple metabolic pathways in the urban ecosystem including food provisioning (Zezza & Tasciotti, 2010), regulation of local microclimate and hydrology (Oberndorfer et al, 2007), consumption of nutrient rich "waste" water and biosolids/organic matter (Armstrong, 2009;de Zeeuw et al, 2011;Smit & Nasr, 1992), and fixation of atmospheric nitrogen (Herridge et al, 2008) and carbon (Beniston & Lal, 2012). For pollinators and other wildlife, habitat is created in the city (Goddard et al, 2010). It has been suggested that UA can also alleviate poverty (van Veenhuizen & Danso, 2007;Zezza & Tasciotti, 2010), increase resiliency (to market fluctuations and climate change) (de Zeeuw et al, 2011), serve as a repository of agricultural knowledge (Koohafkan & Altieri, 2010) and an incubator of new technologies (Despommier, 2010), provide measurable improvements to human health and wellbeing (Joye, 2007;Ulrich, 2006), and reunite urbanites with natural systems from which they have been separated (McClintock, 2010;Turner, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The process of urbanization is one of the most important factors affecting natural ecosystems at the beginning of the 21 st century (Ricketts and Imhoff 2003;Goddard et al 2010). Urban areas of the world are expected to absorb all the human population growth expected over the next four decades (United Nations 2011), and as urban populations expand, so do urbanized landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Ants, arthropod predators and microbial communities are the major regulators of pest populations in urban soils and they can probably be harnessed to control insect pests affecting UA (Yadav et al 2012;Gardiner et al 2014). These studies suggest that, when integrated in the network of gardens and green space in the urban landscape (Goddard et al 2010;Cameron et al 2012), UA can contribute to the conservation of biodiversity and its regulating services in the urban ecosystem.…”
Section: Additional Regulating Servicesmentioning
confidence: 92%